Search for radio halos in starburst galaxies - Galante, Camila Ailen (2024)
Starburst galaxies are undergoing intense episodes of star formation. In these galaxies, gas is ejected into the surrounding environment through winds created by the effect of hot stars and supernova explosions. When interacting with the intergalactic medium, these winds can produce strong shocks capable of accelerating cosmic rays. The radiation from these cosmic rays mainly occurs in radio and gamma rays. The radio halo can be characterized using the scale height. We searched for the presence of radio halos in a sample of edge-on starburst galaxies gathered from the MeerKAT 1.28 GHz Atlas of Southern Sources in the IRAS Revised Bright Galaxy Sample. We selected a sample of 25 edge-on galaxies from the original sample and modeled their disk and halo contributions. We have detected and characterized 11 radio halos, seven of which are reported here for the first time. We found that the halo scale heights increase linearly with the radio diameters and this relation does not depend on the star formation rate. All galaxies in our sample follow the radio-infrared relation with a q parameter value of 2.5±0.1. The dependence of the halo luminosity on the star formation rate and the infrared luminosity supports the hypothesis that the radio halos are the result of synchrotron radiation produced by relativistic electrons and points toward the fact that the star formation activity plays a crucial role in halo creation. The average scale height of 1 kpc implies a dynamical range of 4 Myr, several orders of magnitude greater than the synchrotron losses for electrons of 10 TeV. This suggests that some process must exist to reaccelerate cosmic rays in the halo if gamma-ray emission of a leptonic origin is detected from the halo. According to the relation between the radio and gamma-ray luminosities, we found that NGC 4666 is a potential gamma-ray source for future observations.